Motives for Mergers and Acquisitionsin the Banking Sector - A case study of Royal Bank of Scotland and National Westminster Bank - Dr. Adel Ahmed (International Journal of Advanced Science and Technology, 2020)
Since few decades, Mergers and Acquisitions (M&A) is expanding as a trend and playing an important role in corporate world, world wide. The terms ‘mergers’, ‘acquisition’, and ‘takeover’ affect on many people’s lives directly or indirectly. And in this globalisation era, Mergers and Acquisitions is become a way for expansion and growth in corporate world. There are several factors which affect these types of activities, including motives and reasons behind M&A activity. Because, there are several examples of successful mergers and acquisitions lead firms to be merged or acquire another firm to enlarge their businesses. Moreover, this activity creates a big transaction between two firms, like up to millions of pounds. As a result, it affects to the economy of the world. Besides, those mergers of larger firms give firms a market power which also affects several individuals in markets.